2017
DOI: 10.3892/br.2017.862
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-20a is a promising biomarker for gastric cancer

Abstract: Gastric cancer (GC) is a common type of cancer, particularly in China. Numerous studies have demonstrated that circulating microRNAs (miRNAs) have potential applications as noninvasive biomarkers for cancer diagnosis and prognosis. Microarray-based serum miRNA profiling was performed on the serum of 12 paired pre- and post-operative GC patients to screen differentially expressed serum miRNAs. Twelve different serum miRNAs between pre- and post-operative GC patients were identified. Those miRNAs were verified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 23 publications
0
43
2
Order By: Relevance
“…It was reported that miR-20a was highly expressed in hepatocellular carcinoma [43], lung cancer [44], colon cancer [45] and other tumors [46,47] and acts as an oncogene. And miR-20a can be used as a biomarker in the diagnosis and prognosis of GC [48,49]. Combination of the above studies and reports, it suggested that miR-20a-5p was the most possible candidate to regulate WTX expression and effect GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-20a was highly expressed in hepatocellular carcinoma [43], lung cancer [44], colon cancer [45] and other tumors [46,47] and acts as an oncogene. And miR-20a can be used as a biomarker in the diagnosis and prognosis of GC [48,49]. Combination of the above studies and reports, it suggested that miR-20a-5p was the most possible candidate to regulate WTX expression and effect GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…miR-20a is an important molecule in a variety of biological processes and in cancer progression. Previous studies have shown that the serum exhibits high miR-20a expression and has been indicated to be associated with poor prognosis in patients with nasopharyngeal carcinoma and gastric cancer (44,45). A study has shown that miR-20a can directly target run-related transcription factor 1 to attenuate cell-death in cervical cancer cells by preventing natural killer (NK) cells from releasing interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α), which promote tumor growth (46).…”
Section: Microrna-20a Overviewmentioning
confidence: 99%
“…The observed in our study negative correlation of TIMP3 with miR-20a expression (both preoperative and postoperative miR20a in SCC subtype, post miR20a in the entire study cohort), can be explained as epigenetic silencing of the genes controlling the ECM remodeling. The miR-20a action has been previously linked to the induction of vascular changes in invasive breast carcinomas (48) and metastasis in gastric cancer (50). TIMP3 silencing mediated by miR-20a may be treated as a hallmark of substantial ECM deregulation already present in the NLNT.…”
Section: The Correlations Of Gene and Mir Expressionmentioning
confidence: 99%